2008
DOI: 10.1176/ps.2008.59.7.753
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Prospective Long-Term Treatment Adherence Among Individuals With Bipolar Disorder

Abstract: Nonadherent individuals with bipolar disorder received less intensive pharmacologic treatments, had more suicide attempts, and experienced more barriers to care than adherent individuals. Nonadherence may have system as well as patient components. Consideration of nonadherence as a function of both patient factors and system factors will enhance our ability to understand nonadherence and intervene more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…Age, gender, and race have been found to be associated with adherence status in some studies [8,22] but did not differ statistically between categories of patients who were generally adherent versus nonadherent in other studies [23]. One study found marriage to be positively associated with adherence to medication [24].…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Age, gender, and race have been found to be associated with adherence status in some studies [8,22] but did not differ statistically between categories of patients who were generally adherent versus nonadherent in other studies [23]. One study found marriage to be positively associated with adherence to medication [24].…”
Section: Demographic Factorsmentioning
confidence: 99%
“…In order to obtain a real-world generalizable sample of patients with bipolar disorder, we established minimal exclusion criteria (inability to provide informed consent and inability to be rated on psychiatric rating scales), similar to prior randomized controlled trials of collaborative care management models (14,17). The study was approved by the local institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, clinical characteristics usually associated with poor outcome, such as substance abuse, have not been reported to correlate with diminished LGP participation or success. Moreover, collaborative chronic care management models that have been adapted for bipolar disorder and that include LGP have shown significant improvements in clinical outcome (1417), function (15), and quality of life (15) in long-term, multisite, randomized controlled trials.…”
mentioning
confidence: 99%
See 2 more Smart Citations